The Birds' River dolerite complex - Booth, P W K (Rhodes University, Faculty of Science, Department of Geology, 1971)
A plug-like intrusion of Karroo dolerite, near Dordrecht in the Eastern Cape of the Republic, is described. Field mapping with the, aid of aerial photographs has revealed that the contact of the intrusion, for the most part, dips very steeply outwards. In the south- eastern and eastern areas, however, sheet- or sill-like forms appear to be given off from the main intrusion. In plan view the intrusion is roughly oval shaped, its longer axis being aligned in a north-westerly direction. Its surface area measures approximately 60 square kilometres (24 square miles). A large number of xenoliths composed exclusively of Stormberg sediments, pyroclastic rocks and minor lavas, are to be found cropping out within the dolerite intrusion. These xenoliths, many of which occur in positions far above or below their normal stratigraphic elevation, are extremely variable in size - the largest having an area of approximately 15 square kilometres (6 square miles). The xenoliths represent fragments of the original "roof" of sediments and pyroclastics which have collapsed into and been engulfed by the dolerite magma. This type of dolerite intrusion is known as a "belljar" intrusion. A superficial classification of the dolerites, based chiefly on textural and certain mineralogical features, is presented. In the area surrounding the main intrusion are a number of dolerite dikes and sheets. The youngest phase of igneous activity is represented by the Dragon's Back dike, which cuts across the complex in a north-westerly direction. Several veining phenomena, as well as an interesting variety of metamorphic and metasomatic rocks, are associated with the main dolerite intrusion. Six diatremes are situated in the vicinity of the intrusion. Pyroclastic rocks are represented by a variety of types, and are to be found outside the area of the intrusion, and as xenoliths within it. A tentative interpretation of the mechanism of formation of the intrusion, which appears to be related to volcanic activity and cauldron subsidence, is presented.
Keywords: Diabase; Diabase -- South Africa -- Cape of Good Hope -- Dordrecht.; Igneous rocks -- South Africa